In search of justice: Untold tales of domestic violence survivors - Sultan, Maheen; Akter, Marufa; Mahpara, Pragyna; Pabony, Nuha Anoor; Tasnin, Fariha; Hossain, Sara; Titir, Abdullah; Siddiki, Esrat Jahan; Antor, Sadiul Islam (BIGD and GIZ Bangladesh, 2024)
This book chapter was published in the book named In Search of Justice: Untold Tales of Domestic Violence Survivors and the definite version is available at : https://bigd.bracu.ac.bd/wp-content/uploads/2022/03/Book-In-Search-of-Justice-Eng-Final.pdf